A Multimodal Discourse Analysis of Visual Illustrations Related to COVID-19 Awareness in Nigeria - AMODU, Abideen David; OTESILE, Ayodeji Ebunoluwa (Linguistics and Literature Review, 2023)
The current paper aims to discuss the impact of visual illustrations related to the COVID-19 pandemic in Nigeria. To embark, this study utilizes visual resources, precisely images to facilitate a massive audience by incorporating various modes of visual communication, such as graphics, typography, and attractive layouts to engage the public. This study deploys a multimodal discourse analysis of selected COVID-19 pandemic visual illustrations. The current study examines ten (10) COVID-19 visual illustrations. These /visual illustrations were collected from the official website of the Nigeria Centre for Disease Control (NCDC). This research identified that in creating awareness concerning the spread of the COVID-19 pandemic and its mitigation, there is a dire need to enhance modes of communication using multiple modes of awareness, such as images such as graphics, typography, and other semiotic resources. To elaborate further a large range of visual resources were utilized to analyse the linguistic efficiency of selected visual resources to communicate with the larger audience with concise language and expression. When multiple modes are used effectively in the images, they become audience-affective, such that the attention of the reader or target audience is drawn to the content of the image. Moreover, this study recommended that to achieve the maximum effect of awareness concerning the COVID-19 pandemic, multiple modes model should be used by communicators to facilitate the larger audience Furthermore, it should be used in such a way that they are harmonised and interrelate, contributing to the realisation of meaning throughout the text.